2017
DOI: 10.1039/c7ra00526a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and exceptional adsorption performance of porous MgO derived from a metal–organic framework

Abstract: Porous MgO-hex and MgO-dhp materials were synthesized by annealing metal–organic framework [NH4][Mg(HCOO)3], and exhibit excellent adsorption capacities toward Congo red.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…40 The catalytic applications of this material have attracted a lot of research in different disciplines in recent years. [41][42][43][44] Thus, the importance of MgO in several applications and the emergence of novel phenomena makes it a preferred choice for this investigation. Moreover, the NEAXFS spectra of the MgO system are sensitive to any external treatment [45][46][47][48] and are able to give layer-by-layer information on thin lms.…”
Section: Introductionmentioning
confidence: 99%
“…40 The catalytic applications of this material have attracted a lot of research in different disciplines in recent years. [41][42][43][44] Thus, the importance of MgO in several applications and the emergence of novel phenomena makes it a preferred choice for this investigation. Moreover, the NEAXFS spectra of the MgO system are sensitive to any external treatment [45][46][47][48] and are able to give layer-by-layer information on thin lms.…”
Section: Introductionmentioning
confidence: 99%
“…The superior maximum adsorption value of 2375 mg g À1 towards CR adsorption in solution at various initial concentrations in the range of 400-1400 mg L À1 for 1 h at natural pH and room temperature on the as-obtained MgO adsorbent was nearly equal to the reported superhigh adsorption capacity, 1,30 which was superior to that in most reports. 16,25,28,37 This showed that MgO nanoparticles prepared via the facile solvent-free chemical reaction manifested outstanding adsorption properties.…”
Section: Characterization Of Mgo Nanoparticlesmentioning
confidence: 97%
“…In solution, CR would be adsorbed to the surface of MgO through a neutralization reaction. 28 To determine the surface basicity of the prepared MgO samples, temperature-programmed desorption (TPD) of CO 2 curves were obtained, as shown in Fig. 2c.…”
Section: Factors Inuencing Adsorption Performance On Mgo Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations